Formation of winter wheat productivity under different nitrogen nutrition systems (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
Abstract. Formulation of the problem. Efficient nitrogen nutrition is a key factor determining winter wheat productivity, particularly under early spring application on frozen-thawed soil. However, the comparative effectiveness of different nitrogen fertilizer forms and their influence on yield structure formation, grain productivity, and grain quality, as well as varietal responses, remain insufficiently studied and require further scientific substantiation. Purpose. The aim of the study was to determine the effect of different forms of nitrogen fertilizers applied in early spring on frozen-thawed soil on the formation of yield structure components, grain yield, and grain quality of winter wheat under conditions of the Left-Bank Forest-Steppe of Ukraine. Research methods. A field experiment was conducted in 2024–2025 at the farm “Fortuna” (Atemivka village, Chuhuiv district, Kharkiv region). The experiment was established in three replications using a split-plot design. Factor A included winter wheat varieties Kvitka poliv and Yuson. Factor B included nitrogen fertilizer treatments: unfertilized control, ammonium nitrate, UAN-28, urea, and ammonium sulfate. Crop management practices were standard for the region, except for the studied factors. Research results. The results showed that both varietal characteristics and nitrogen fertilizer forms significantly affected the formation of yield components in winter wheat. Under the control treatment, productive stem density was 412 stems/m² for Kvitka poliv and 395 stems/m² for Yuson, thousand grain weight was 38.6 g and 37.0 g, and grain protein content was 10.8% and 10.2%, respectively, indicating insufficient nitrogen supply during early spring growth. All nitrogen fertilizer treatments significantly improved crop performance. Productive stem density increased to 468–498 stems/m² in Kvitka poliv and 452–480 stems/m² in Yuson. The highest values were obtained with ammonium nitrate (498 and 480 stems/m²), due to the rapid availability of nitrate nitrogen and stimulation of tillering during spring regrowth. UAN-28 provided 487 and 470 stems/m², ammonium sulfate 482 and 465 stems/m², while urea resulted in the lowest values (468 and 452 stems/m²) due to slower transformation of amide nitrogen. A similar trend was observed for thousand grain weight, which increased to 40.1–41.2 g in Kvitka poliv and 38.8–39.8 g in Yuson. The highest values were recorded under ammonium nitrate application (41.2 and 39.8 g), while the lowest among fertilized variants were observed with urea. Grain protein content increased to 11.9–13.1% in Kvitka poliv and 11.3–12.5% in Yuson. The highest protein content was obtained under ammonium sulfate application, which is associated with the positive role of sulfur in nitrogen assimilation and protein synthesis. Ammonium nitrate and UAN-28 provided intermediate values, while urea showed the lowest improvement among fertilized treatments. Winter wheat grain yield increased significantly under nitrogen fertilization, from 4.21 to 5.03 t/ha in Kvitka poliv and from 3.98 to 4.78 t/ha in Yuson. The highest yield increase was obtained with ammonium nitrate (0.82 and 0.80 t/ha) with nitrogen use efficiency of 34% and 33%, respectively. UAN-28 ensured yields of 4.99 and 4.73 t/ha, ammonium sulfate 4.96 and 4.70 t/ha, while urea showed the lowest efficiency among fertilized variants. Varietal analysis demonstrated that Kvitka poliv consistently outperformed Yuson across all studied parameters, indicating a higher realization of its biological potential under improved nitrogen nutrition conditions. Conclusions. Thus, early spring nitrogen fertilization significantly influences yield formation and grain quality of winter wheat. Ammonium nitrate and UAN-28 were the most effective for increasing grain yield, while ammonium sulfate ensured the highest grain protein content. Urea showed the lowest efficiency under early spring conditions. The obtained results confirm the importance of selecting appropriate nitrogen fertilizer forms depending on production goals and environmental conditions.
Keywords: winter wheat; nitrogen fertilizers; ammonium nitrate; UAN-28; urea; ammonium sulfate; yield; grain quality; protein content; frozen-thawed soil